The best American travel writing 2002 - Mayes, Frances (Boston, MA : Houghton Mifflin Co., 2002)
A collection of 26 selections chosen from newspapers and periodicals.
In the land of the white rajahs / Lawrence Millman -- Lambs of God and the new math / Toni Mirosevich -- Ancient roads, walled cities / Tom Mueller -- Where the bee sucks / Elizabeth Nickson -- Home for dinner / Molly O'Neill -- Zion's vital signs / P.J. O'Rourke -- Spain in a minor key / Tony Perrottet -- Making rain /Kira Salak -- The man upstairs / David Sedaris -- Stolen blessings / Thomas Swick -- Spetses, Greece / Isabella Tree -- The fist of God / Kate Wheeler.
Keywords: Travel -- Periodicals -- Excerpts; Travel writing, American